2008
DOI: 10.1111/j.1479-8301.2008.00227.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of risperidone in the treatment of delirium in elderly patients

Abstract: Background: Despite increasing recognition of delirium as a serious complication of physical illness, little has been reported in this area. Interest has been raised in treatment options other than haloperidol, such as atypical antipsychotic agents. Methods: A 2-week open-label trial of risperidone for the treatment of delirium was conducted to assess the efficacy and tolerance of this medication in elderly patients. Twenty-two patients with DSM-IV-defined delirium were investigated. All patients had the hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Ikezawa et al [14] prospective, open label study 22 elderly subjects with DSM-IV hyperactive delirium with mean baseline DRS score at 20.7 ± 3.0 fi xed dose 0.5 -3 mg (mean 1.5 ± 0.7) DRS -mean duration for delirium resolution was 4.0 ± 2.9 days.…”
Section: Olanzapinementioning
confidence: 97%
“…Ikezawa et al [14] prospective, open label study 22 elderly subjects with DSM-IV hyperactive delirium with mean baseline DRS score at 20.7 ± 3.0 fi xed dose 0.5 -3 mg (mean 1.5 ± 0.7) DRS -mean duration for delirium resolution was 4.0 ± 2.9 days.…”
Section: Olanzapinementioning
confidence: 97%
“…The Ser9Gly polymorphism of dopamine receptor D3 (DRD3) could disturb the membrane insertion of Psychiatry and Clinical Neurosciences 2011; 65: [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Pharmacogenomics of schizophrenia 7 this receptor molecule with biological consequence. Studies with FGA treatment response showed the Gly allele is more frequent among poor responders, however, recent studies with SGA showed a positive link of the Gly allele with a better response.…”
Section: Dopamine Receptor D3mentioning
confidence: 99%
“…The neurobiology of DISC1 in the normal developing and adult brain and its roles in SCZ are not well understood. The biological role of DISC1 is, however, speculated from the following findings: (i) downregulation of DISC1 accelerates morphological development of adult-born neurons resulting in soma hypertrophy and enhancement of dendritic outgrowth; (ii) inhibition of DISC1 leads to mispo-Psychiatry and Clinical Neurosciences 2011; 65: [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Pharmacogenomics of schizophrenia 9 sitioning of new neurons in the molecular layer from overextended migration, suggesting that DISC1 serves as an interpreter that relays positional signals to the intracellular migratory machinery rather than a direct mediator of neuronal migration; (iii) new neurons with DISC1 knockdown exhibit more mature neuronal firing patterns; and (iv) downregulation of DISC1 accelerates synapse formation of newborn neurons. Taken together, these results indicate that DISC1 controls the tempo of the entire process of neuronal integration in the adult brain as a master regulator.…”
Section: Disrupted In Schizophreniamentioning
confidence: 99%
See 2 more Smart Citations